Evaluation of the Degree of Agreement of Four Methods for Diagnosing Diabetic Autonomic Neuropathy - Peng, Yu; Liu, Ying-shan; Wu, Min-yi; Chen, Chu-na; Li, Chu-qiao; Jiang, An-qi; Li, Chong-xin; Wang, Yao; Tian, Ge; Pan, Su-yue; Xu, Ling-ling (Frontiers in Neurology, 2021)
Background: There are many methods to diagnose diabetic autonomic neuropathy (DAN); however, often the various methods do not provide consistent results. Even the 2 methods recommended by the American Diabetes Association (ADA) guidelines, Ewing’s test and heart rate variability (HRV), sometimes give conflicting results. The purpose of this study was to evaluate the degree of agreement of the results of the Composite Autonomic Symptom Score 31 (COMPASS-31), skin sympathetic reaction (SSR) test, Ewing’s test, and HRV in diagnosing DAN. Methods: Patients with type 2 diabetes were recruited and each received the COMPASS-31, SSR, Ewing’s test, and HRV for the diagnosis of DAN. Patients were categorized as DAN(+) and DAN(-) by each of the tests. Kappa consistency tests were used to evaluate the agreement of diagnosing DAN between any 2 methods. Spearman’s correlation test was used to evaluate the correlations of severity of DAN between any 2 methods. Receiver operating characteristic (ROC) analyses were used to evaluate the diagnostic value and cut-off value of each methods. Results: A total of 126 type 2 diabetic patients were included in the study. The percentage of DAN(+) results by HRV, Ewing’s test, COMPASS-31, and SSR was 61%, 40%, 35%, and 33%, respectively. COMPASS-31 and Ewing’s test had the best agreement for diagnosing DAN (kappa = 0.512, p < 0.001). COMPASS-31 and Ewing’s test also had the best correlation with respect to severity of DAN (r = 0.587, p < 0.001). Ewing’s test and COMPASS-31 had relatively good diagnostic value (AUC = 0.703, 0.630 respectively) in ROC analyses. Conclusion: COMPASS-31 and Ewing’s test exhibit good diagnostic consistency and severity correlation for the diagnosis of DAN. Either test is suitable for diagnosis of DAN, and treatment follow-up.